Johannes Pauli and His Social Criticism. A Past Voice for Our Own Time? Pedagogical Reflections on the Relevance and Usefulness of Sixteenth-Century Sermon Narratives Until Today - Classen, Albrecht (Biuletyn Historii Wychowania, 2023)
Contrary to many Menetekels as to the demise of the Humanities and hence the study of pre-modern literature, an open-minded and more flexible approach to the history of literature strongly suggests that there are many opportunities for the future classroom invested in the topic of human interaction, social and ethical agendas, and communication. In fact, if we recognize the literary archive as a storehouse of ideas, experiences, and concepts regarding the challenges of the human existence, we face a highly productive epistemological opportunity building intellectual, ethical, and moral bridges between the past and the present. Drawing from the enormously popular sermon stories by the Franciscan Johannes Pauli, this study demonstrates the timeless value of his narratives and hence an intellectual promise for contemporary students, still developing and ascertaining the labyrinth they live in. As Pauli certainly proves conservative, his Schimpf und Ernst provides a fascinating compass for those who have realized the many shortcomings and failures in society, Eastern or Western, including our contemporary, seeking alternative voices strongly grounded in timeless and universal human values.